Perinatal presentations of non‐immune hydrops fetalis due to recessive PIEZO1 disease: A challenging fetal diagnosis. Issue 5 (12th December 2022) - Ghesh, Leïla; Désir, Julie; Haye, Damien; Le Tanno, Pauline; Devillard, Françoise; Cogné, Benjamin; Marangoni, Martina; Tecco, Laura; Heron, Delphine; Le Vaillant, Claudine; Joubert, Madeleine; Beneteau, Claire
Abstract: Hydrops fetalis is a rare disorder associated with significant perinatal complications and a high perinatal mortality of at least 50%. Nonimmune hydrops fetalis (NIHF) is more frequent and results from a wide variety of etiologies. One cause of NIHF is lymphatic malformation 6 (LMPHM6) due to biallelic loss‐of‐function (LoF) variants in PIEZO1 . Most individuals are diagnosed postnatally and only few clinical data are available on fetal presentations. We report six novel biallelic predicted LoF variants in PIEZO1 identified by exome sequencing in six fetuses and one deceased neonate from four unrelated families affected with LMPHM6. During the pregnancy, most cases are revealed by isolated NIHF at second trimester of gestation. At post‐mortem examination ascites, pleural effusions and telengectasies can guide the etiological diagnosis. We aim to further describe the perinatal presentation of this condition which could be underdiagnosed. Abstract : Lymphatic malformation 6 is characterized by a uniform, widespread lymphedema affecting all segments of the body and of varying severity. This condition is due to bi‐allelic loss‐of‐function (LoF) variants in PIEZO1 . Up to now, 21 LMPHM6 families have been reported corresponding to 33 affected individuals. Most of LMPHM6 individuals were diagnosed postnatally, with poor clinical data available about fetal presentation. In this manuscript, we further describe the perinatal presentations and/or the autopsies of six fetuses and one neonate from four unrelated families affected with LMPHM6. We also describe six new LoF variants in PIEZO1 identified by exome sequencing.